Plan de formación para el manejo de entornos virtuales para los docentes de la Universidad de Guayaquil - Merchán Riera, Jorge Misael (2018)
This article aims to present a proposal for training for university teachers to enable them to handle virtual environments to support the processes of teaching and learning at theUniversity of Guayaquil in Ecuador; specifically in the career in Computerized Management Systems Engineering at the Faculty of Administrative Sciences. A descriptive research, field study and transectional was held to design the training plan that aims to apply in 2018. It is concluded that it is necessary that this training is an essential part of the career plan for teachers at the University of Guayaquil, to contribute to the training required by this new millennium